Data on bioactive peptides derived from chicken hydrolysate with potential alcohol dehydrogenase stabilizing activity and in silico analysis of their potential activity and applicability - Chuqiao Xiao (Data in Brief, 2020)
Bioactive peptides have attracted extensive attention worldwide as natural alternatives to promote human health and wellness. Previous studies have shown that chicken hydrolysates could enhance alcohol dehydrogenase, and subsequently they facilitate alcohol metabolism and ameliorate alcohol-induced liver injury. The data presented in this article support the accompanying research article “Isolation and identification of alcohol dehydrogenase stabilizing peptides from Alcalase digested chicken breast hydrolysates”. Present article details all 82 peptides identified from the most active fractions of chicken hydrolysates, and 154 peptides from in silico digestion of the 82 identified peptides, together with the prediction of their potential bioactivity and applicability using several in silico assays. Keywords: Bioactive peptides, Chicken breast, Alcohol dehydrogenase stabilizing, LC-MS/MS, In silico analysis